Reflections on the Adaptation of a Postgraduate Degree in Water Management from In‐person to Remote Delivery. (10th September 2022) - Clamen, Murray; Anderson, Emma; Dipple, Johanna; Adamowski, Jan
Abstract: In early 2020, the COVID‐19 pandemic spurred the rapid adaptation of university course delivery to an online format. Though in‐person delivery partially resumed in the Fall of 2021, future conditions may favor a return to, or addition of, remote delivery. It is therefore important for instructors, program directors, and institutions to capitalize on this learning opportunity and reflect on adaptation measures' successes (and failures) to inform future online course design. The reworking of McGill University's Master of Science Program in Integrated Water Resources Management (IWRM) provides a case study to evaluate the adaptation of remote teaching of water resource management. Informed by the Community of Inquiry (CoI) framework with a focus on preserving transferable skills, a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was used to evaluate the five core program components. This evaluation framework, which can be applied to most university programs, resulted in several widely relevant insights. For example, remote delivery can create opportunities for greater participation of international students as it eliminates the need for translocation costs. Likewise, a larger variety of guest speakers can participate remotely, giving students greater exposure to different water career paths and research perspectives, ultimately strengthening the program. However, several weaknesses pose threats to online learning. The standard in‐person lecture‐style format must therefore be amended to maintain engagement and facilitate student‐to‐student and student‐to‐instructor learning processes. Course components that can enhance the online experience include breakout rooms, discussion boards, frequent journals/feedback forms, online activities, breaks, virtual office hours, and multi‐media presentations.